2013
DOI: 10.1111/twec.12095
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Volatility and Intra‐Asia Trade: Evidence by Type of Goods

Abstract: This paper examines the impact of intra‐Asia exchange rate volatility on intra‐Asia trade in primary goods, intermediate goods, equipment goods and consumption goods from 1980 to 2009. For Asia, the evidence shows that as intraregional exchange rate volatility increases, intraregional exports in these goods fall. This adverse impact is even more pronounced in the subregion of Association of Southeast Asian Nations (ASEAN)+5 comprising ASEAN member countries plus the People's Republic of China; Hong Kong, China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
(46 reference statements)
0
19
0
4
Order By: Relevance
“…Recent empirical studies, however, have found that the exchange rate volatility has significantly negative effect on intra‐Asian trade (e.g. Thorbecke, ; Hayakawa and Kimura, ; Chit et al ., ; and Tang, ). These studies focused on a particular industry (electronic components in Thorbecke, ), and the difference between final and intermediate goods (Hayakawa and Kimura, ; and Tang, ).…”
Section: Introductionmentioning
confidence: 96%
“…Recent empirical studies, however, have found that the exchange rate volatility has significantly negative effect on intra‐Asian trade (e.g. Thorbecke, ; Hayakawa and Kimura, ; Chit et al ., ; and Tang, ). These studies focused on a particular industry (electronic components in Thorbecke, ), and the difference between final and intermediate goods (Hayakawa and Kimura, ; and Tang, ).…”
Section: Introductionmentioning
confidence: 96%
“…The positive effects of volatility on bilateral trade flows were apparent between USA and Brazil in various industries (Bahmani-Oskooee, Harvey and Hegerty, 2013). Likewise, the favourable effects of exchange rate volatility were also found on trade flows among the countries in South Asia (Tang, 2014). Nonetheless, while the positive impact of volatility presented on trade of machinery and transport equipment between Japan and USA, it showed mixed results on chemicals products and miscellaneous manufactured articles (Bahmani-Oskooee and Hegerty, 2008).…”
Section: Studies In General Casesmentioning
confidence: 99%
“…6 As can be seen in Figure 2, the share of currencies invoiced in 5 For recent estimates of the weights of the dollar in East Asian countries' hypothetical currency baskets see Henning (2012). 6 Empirical analysis by Hayakawa and Kimura (2008), Volz (2010), Tang (2011) and Thorbecke (2011) shows that exchange rate volatility has negative effects on intra-regional trade in the East Asian region, and that volatile exports of Asian and Pacific countries (excluding Japan) has been constantly above 80 percent, that is, a very large share of the trade within the regional trade-production network is being conducted in dollar.…”
Section: The Dollar's Role In East Asiamentioning
confidence: 99%